HISTORICAL AND SCIENTIFIC ASPECTS OF CREATING THE THIRD RENAISSANCE IN UZBEKISTAN - Musurmankulov Farkhod Uralovich (American Journals, 2024)
The article is based on the analysis of historical sources, according to which the spirituality and education of the peoples of the Turan land in the 9th-12th and 12th-14th centuries were the period of the Eastern 1-2-Renaissance and were recognized by the whole world. Also, analytical data on the positive works of great thinkers and scientists who lived in the East and left us a rich scientific and spiritual heritage, in the places of science, culture and education, are historical facts, and the work carried out in Uzbekistan in the field of science, culture and education is recognized as the beginning of the stage of the third Renaissance.
Keywords: Turan, Movaraunnahr, Turkestan, spirituality, education, science, art, culture and enlightenment.